2019
DOI: 10.1097/dss.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Split-Face, Evaluator-Blind Clinical Trial Comparing Monopolar Radiofrequency Versus Microfocused Ultrasound With Visualization for Lifting and Tightening of the Face and Upper Neck

Abstract: BACKGROUND Over the past decade, 2 major modalities for noninvasive skin tightening have emerged: monopolar capacitive-coupled radiofrequency (MRF) and microfocused ultrasound with visualization (MFU-V). Up to date, no comparative clinical trials have been performed. OBJECTIVE To compare the efficacy and safety of MRF versus MFU-V for the lifting and tightening of the face and neck. MATERIALS AND METHODS Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
0
28
0
2
Order By: Relevance
“…Layering different depths of coagulation points has been studied as an optimal method for simultaneously contracting the deeper fascial layers at depths of 3 (7‐mHz transducer) and 4.5 mm (4‐mHz transducer), while stimulating dermal collagen at more superficial depths of 1.5 and 2 mm [ 12 ]. Comparison studies have shown no difference in efficacy with regards to MFU and monopolar radiofrequency in the improvement in facial/neck skin laxity [ 13 ]. However, even with layering techniques, MVU‐targeted, thermally coagulated tissue does not reach the same volume of the treated tissue as microneedle fractional RF, as previously mentioned in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Layering different depths of coagulation points has been studied as an optimal method for simultaneously contracting the deeper fascial layers at depths of 3 (7‐mHz transducer) and 4.5 mm (4‐mHz transducer), while stimulating dermal collagen at more superficial depths of 1.5 and 2 mm [ 12 ]. Comparison studies have shown no difference in efficacy with regards to MFU and monopolar radiofrequency in the improvement in facial/neck skin laxity [ 13 ]. However, even with layering techniques, MVU‐targeted, thermally coagulated tissue does not reach the same volume of the treated tissue as microneedle fractional RF, as previously mentioned in this article.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that RF was superior for improving photoaging and flaccidity only when compared to non‐treatment. Compared with other therapies, the results were similar between the treatments tested, with no RF superiority in any of the situations 17‐20 …”
Section: Resultsmentioning
confidence: 77%
“…The most common side effects of MFU are transient pain, erythema, edema, and bruising, which typically last for a few days [66,71] . A study of 49 patients of Fitzpatrick skin type III to IV observed 2 cases of postinflammatory hyperpigmentation on the forehead at 1 month, but not at 6 months [71] . Nerve and bone irritation are rarely encountered, as the frequency of the transducer fixes the depth of penetration.…”
Section: Microfocused Ultrasoundmentioning
confidence: 99%